An anticoagulant fucan sulfate with hexasaccharide repeating units from the sea cucumber Holothuria albiventer. (15th July 2018) - Cai, Ying; Yang, Wenjiao; Yin, Ronghua; Zhou, Lutan; Li, Zhongkun; Wu, Mingyi; Zhao, Jinhua
Abstract: A fucan sulfate was isolated and purified from the sea cucumber Holothuria albiventer by papain enzymolysis, alkaline hydrolysis and ion-exchange chromatography. The water-soluble polysaccharide had high molecular weight and contained fucose and sulfate in a molar ratio of about 1:0.83. Methylation analysis of the native polysaccharide indicated that its glycosidic linkages and sulfate substituents might be at O- 3 or O -3, 4 or O -2, 3, or O -2, 3, 4 positions. FT-IR and 2D NMR spectroscopies further revealed that the fucan sulfate is characteristically composed of a regular α (1 → 3) linked hexasaccharide repeating unit which is substituted with sulfate esters in a distinctive pattern. Anticoagulant properties of the fucan sulfate and its depolymerized product were assessed in vitro in comparison with a low-molecular-weight heparin. The fucan sulfate exhibits strong APTT and TT prolonging activities and intrinsic factor Xase inhibitory activity, and its molecular size seemed to be required for these activities. Graphical abstract: Highlights: A new polysaccharide was purified from the sea cucumber Holothuria albiventer . The polysaccharide was analyzed by chemical and instrumental methods. The fucan sulfate comprises of regular α(1. → 3)-linked hexasaccharide repeats The fucan sulfate exhibits strong biological activities.